Research Note: Effects of cage and floor rearing systems on growth performance, carcass traits, and meat quality in small-sized meat ducks - H. Bai (Elsevier, 2022)
ABSTRACT: This study was performed to evaluate the effects of different rearing methods on the growth performance, carcass yield, and meat quality of small-sized meat ducks. A total of 420 healthy 21-day-old birds was randomly allocated to 2 treatment groups (6 replicates per treatment, sex ratio 1/1) and subjected to 2 rearing methods (furnished cage and plastic wire-floor) until d 63. Growth performance was measured in all birds. Three males and 3 females from each replicate were randomly selected and evaluated to determine the carcass yield and meat quality. In terms of growth performance, the rearing method affected the final body weight, average daily feed intake, and average daily gain, which were higher in the cage group (P < 0.05) than in the floor group, with a similar feed/gain in both groups. For slaughter performance, ducks in the cage group showed a higher abdominal fat yield and lower gizzard yield than those in the floor group (P < 0.05). For meat quality, the L* value of the breast muscle was higher in the cage group than in the floor group (P < 0.05). The pH recorded at 1 h was lower and pH recorded at 24 h was higher in the cage group (P < 0.05). The shear force and water loss rate were both lower in the cage group (P < 0.05). Additionally, the moisture content was lower and intramuscular fat content was higher in ducks fed in cages (P < 0.05). Our results indicate that the cage rearing system improved the growth performance and meat quality of ducks, which is appropriate for small-sized meat ducks.